GIS-material for the archaeological project: Settlements outside Fågelsta and Fivelstad - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to the replacing of overhead power lines with underground cable in the area around Fågelsta, Fivelstad, Tråstad, Risberga and Eketorp in Fivelstad parish, Motala municipality, the Swedish National Heritage Board's contract archaeology division, UV Öst, has surveyed three different sections of the area. The field work was conducted during April and May 2005. Prehistoric settlement remains were found in two places, in she shape of hearths, pits, post holes, a possible hut construction and worked quartz. The planned works could continue after the remains had been excavated.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the survey was to conclude whether any archaeological remains were going to be affected by the trenching and, if so, to suggest alternative locations for the laying of cable.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför arbete med att ersätta luftledningar med jordkabel i området runt Fågelsta, Fivelstad, Tråstad, Risberga och Eketorp, samtliga i Fivelstads socken, Motala kommun har Riksantikvarieämbetet UV Öst genomfört arkeologiska utredningar etapp 2 inom tre sträckningar. Fältarbetet utfördes under april och maj 2005. Förhistoriska boplatslämningar framkom på två ställen, i form av härdar, gropar, stolphål, en eventuell hyddkonstruktion samt bearbetad kvarts. De planerade markarbetena kunde genomföras efter arkeologisk undersökning.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Tre sträckor utreddes i syfte att konstatera om de planerade markarbetena skulle komma i konflikt med lagskyddad fornlämning. Syftet med utredningen var också att söka alternativa sträckningar om fornlämning påverkades.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Boplatser utanför Fågelsta och Fivelstad
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi